FUZZY INFERENCE SYSTEM MODELING FOR BED ACTIVE CARBON RE-GENERATION PROCESS (CO2 GAS FACTORY CASE) - S. Febriana; M.D. Kurniawati; Iwan Halim Sahputra; I Nyoman Sutapa (Institute of Research and Community Outreach - Petra Christian University, 2005)
Bed active carbon is one of the most important materials that had great impact in determining level of impurities in production of CO2 gas. In this particular factory case, there is unavailability of standard duration time of heating and cooling and steam flow rate for the re-generation process of bed active carbon. The paper discusses the fuzzy inference system for modeling of re-generation process of bed active carbon to find the optimum setting parameter. The fuzzy inference system was build using real historical daily processing data. After validation process, surface plot analysis was performed to find the optimum setting. The result of re-generation parameter setting is 9-10 hours of heating process, 4.66-5.32 hours of cooling process, and 1500-2500 kg/hr of steam flow rate.